SLEEP QUALITY AMONG INDEPENDENT OLDER PERSON IN COMMUNITY IN MALAYSIA - Akehsan Dahlan; Hanisha Haidzir; Mohamad Ghazali Masuri (Journal of Islamic, Social, Economics and Development, 2021)
Sleep is a basic physiological need. Good sleep is required for a person's overallhealth and well-being. Poor sleep quality often associated with increased risk of mortality,depression, lower cognitive performance, poor self-rated health status and lower quality of life.Epidemiology study indicates that older people often have poor sleep quality due to physicaland psychological conditions. However, the information about sleep quality among the olderperson who lives in the community is inconclusive, especially among the independent olderperson. Hence, this study aimed to determine sleep quality among the independent older personwho lives at home in the community. A cross-sectional study throughout Malaysia wasconducted involving 335 older people from the community. The 19-item Malay version of thePittsburgh Sleep Quality Index (PSQI-M) was used to assess sleep quality. There are 223(66.6%) older persons who are having poor sleep quality (scores above 5 in PSQI-M), and themean (SD) for sleep quality among older person with poor sleep quality is 9.00 (3.87). Inaddition, there was a significant correlation between age with sleep quality (r=-0.24, p<0.00)among older person in the community. Health care professionals should play an importantrole in improving sleep quality among older persons to promote health and well-being.